The Role of Social Media, Family and School in Building Indonesian Values to Multi-Ethnic Students at SMP Negeri 2 Pekalongan - Kusumaningtyas, Nisa; Atmaja, Hamdan Tri; Subagyo, Subagyo (JESS (Journal of Educational Social Studies), 2019)
The interaction among Javanese, Arabic and Chinese students at SMP Negeri 2 Pekalongan requires the role of family and school in creating a harmonious atmosphere amid social media hoax information. This study aims to analyze the role of social media, family, and school in building Indonesian values. This research was conducted qualitatively with a phenomenology approach. Research data sources were students, parents, curriculum representatives, and social studies teachers. The technique of collecting data was through interviews, observations, and study documents that tested their validity through source triangulation techniques. The results of the study indicate that social media was used by students to add insight into Indonesian cultures, such as learning traditions from other regions so that they can appreciate differences. Parents took a role in building Indonesian values ​​through application in daily life, such as teaching the children to respect and tolerate people from other ethnicities or religions; for instance, respecting their neighbors from other religions to carry out their worship. School took a role in building the Indonesian value of children through school programs such as program smile, greet, salutation, polite and courteous. This program requires the students to be friendly and polite to anyone in the school environment.